Green Accounting, Material Flow Cost Accounting, Leverage, Sustainability, Resource Efficiency Perusahaan BEI di Indonesia (Institut Agama Islam Negeri Kudus, 2023)
The study aims to determine the factor that influence sustainability, namely green accounting, material flow cost accounting, leverage and resource efficiency. This study uses quantitative research. This population of this stidy are all companies listed on the Indosesia Stock Exchange. Selection of the sample using purposive sampling obtained a sample of 31 companies according to the specified criteria. Based on multiple inier regression analysis,the results show that green accounting and leverage have no effect on sustainability and material flow cost accounting has an effect on sustainability. based on the moderation regression analysis, the results show that resource efficiency is able to moderate green accounting and leverage on corporate sustainability. meanwhile, resource efficiency is not able to moderate material flow cost accounting for corporate sustainability. The survival of the company is more influenced by material flow cost accounting, this research has implication for companies in roducing policies related to the survival of the company.